The Immobilized Copper on Nickel Ferrite: A Magnetically Superior Nanocatalyst for Chemoselective and Knoevenagel Synthesis of Bisdimedones and 1,8-Dioxo-octahydroxanthenes under Solvent-Free Conditions - Zeynizadeh, Behzad; Rahmani, Soleiman; Hallaj, Arezu (Current organic synthesis, 2019)
Nowadays, bisdimedones and 1,8-dioxo-octahydroxanthenes are considered as biologically active materials. Due to this, the synthesis of the mentioned materials is the subject of more interest. Although most of the reported methods have their own merits, however, they generally require the use of expensive reagents, hazardous organic solvents, a tedious workup procedure and reduced recyclability of the applied catalyst system. Overcoming of the above mentioned drawbacks, therefore, encouraged us to investigate the capability of nanostructured NiFe2O4@Cu towards the synthesis of bisdimedones and 1,8- dioxo-octahydroxanthenes under green reaction conditions. Nanoparticles of NiFe2O4@Cu were prepared via a two-step procedure including the preparation of NiFe2O4 by solid-state grinding of Ni(OAc)2·4H2O and Fe(NO3)3·9H2O in the presence of NaOH followed by the immobilization of Cu(0) on the surface of NiFe2O4 nucleus via hydrazine hydrate reduction of Cu(NO3)2·3H2O. After the synthesis of NiFe2O4@Cu, the catalytic activity of the Cu-nanocatalyst towards Knoevenagel reaction of aromatic aldehydes with dimedone under different reaction conditions was investigated. The examinations showed that using the molar equivalents of aromatic aldehydes (1 mmol) and dimedone (2 mmol) in the presence of 0.15 g NiFe2O4@Cu under solvent-free conditions chemoselectively afforded structurally different bisdimedone products at 60°C and 1,8-dioxo-octahydroxanthenes at 120°C. In this study, magnetically, nanoparticles of NiFe2O4@Cu were prepared and then characterized using different analyses. The catalytic activity of the prepared Cu-nanocatalyst was also studied towards solvent-free Knoevenagel condensation of aromatic aldehydes with dimedone. All the reactions were carried out within 15-240 min to afford bisdimedone and 1,8-dioxo-octahydroxanthene products in high yields.